ANALYSIS OF TRANSPORTATION MODE CHOICE IN MALANG CITY USING MULTINOMIAL LOGISTICS METHOD - Madu Sonia; Meriana Wahyu Nugroho; Titin Sundari; Rahma Ramadhani (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
In every urban area, especially in the Malang area, modes of transportation are increasingly diverse, ranging from private vehicles, public transportation, to online-based transportation. This research aims to determine the choice of transportation mode using the multinominal logistics method. With this type of quantitative research and data sources through surveys conducted in 5 sub-districts of Malang City using the multinominal logistics method. The research results showed that 11% of respondents went from home to another place for work using private transportation, 3% of respondents were still students. 88% of working respondents and housewives chose public transportation, 97% of whom were still students. 9% of respondents who work and are housewives use online vehicles while 0% are still students. Keywords: Daily Activities; Household; Multinomial Logistic Regression; Mode Choice; Spatial.